Anticipatory postural adjustments are modulated by substantia nigra stimulation in people with Parkinson's disease and freezing of gait. (September 2019) - Heilbronn, Melanie; Scholten, Marlieke; Schlenstedt, Christian; Mancini, Martina; Schöllmann, Anna; Cebi, Idil; Pötter-Nerger, Monika; Gharabaghi, Alireza; Weiss, Daniel
Abstract: Background: A precise understanding of the neuronal circuits involved in the control of anticipatory postural adjustments (APAs) for gait initiation is missing. Neurostimulation in Parkinson's disease (PD) provides a method of modulating APAs to gain insight into the underlying circuitry. Objective: Our objective was to investigate if APA kinematics for step initiation could be modulated by high frequency stimulation of the subthalamic nucleus (STN) or substantia nigra pars reticulata (SNr) in people with PD and freezing of gait (FoG). Methods: We studied 14 people with PD and FoG using neurostimulation of the STN and SNr areas after overnight withdrawal of dopaminergic medication on the instrumented stand and walk test. We tested patients in the following randomized conditions: 'off stimulation', 'STN' stimulation (only), and 'SNr' stimulation (only). Patients were blinded to the stimulation condition. The APAs were recorded with inertial sensors and processed offline. Moreover, we assessed clinical scores with respect to motor symptoms, non-motor symptoms, executive function, and FoG. Results: SNr but not STN stimulation modulated the anterio-posterior size of APA. The SNr modulation of APA was associated with the stimulation effect on FoG (trend; r = 0.580, P = 0.102). The APA modulation was not correlated with any other cognitive or clinical measures. Conclusion: Neuromodulation of the SNr but not of the STN modulated APAs in PD patients with FoG. The different effects of STN or SNr on the kinematic parameters of APA support the concept of segregate targets in order to address diverse kinematic components of PD gait. Highlights: We tested the effect of subthalamic or nigral stimulation on gait initiation in Parkinson's disease and freezing of gait. This study identifies neuronal network correlates of first step preparation and -execution. Substantia nigra stimulation modulated the kinematic measures of first step preparation (anticipatory postural adjustment). Anticipatory postural adjustments (anterio-posterior dimension) were reduced with nigral stimulation. They showed a correlation with clinical improvement of freezing of gait as non significant trend; r =0.580, P =0.102).